2019
DOI: 10.1101/725952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency of fiveEscherichia Colipathotypes in Iranian adults and children with acute diarrhea

Abstract: 20Background: knowledge about the distribution of Escherichia Coli (E. coli) pathotypes in Iran is 21 limited to studies with small scale and limited scope. This nation-wide survey aims to provide a 22 more generalizable estimate of pathogenic E. coli distribution in Iran. 23 acute diarrhea cases of 15 provinces. Culture-positive E. coli samples were tested with PCR for 25 detection of five E. coli pathotypes (STEC, ETEC, EPEC, EAEC, and EIEC). Frequency of these 26 pathotypes was estimated for different provi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Our results are consistent with a study conducted in Brazil, which reported a prevalence of 4.4% [30]. Similarly, Iranian studies have reported prevalence rates of 3.1% and 1.8%, respectively [25][26][27][28][29][30][31][32] . whereas it is far a little bit with a study in Colombia, South America 0.29% 34 whereas with the results of CostRica study 19.23%.…”
Section: Resultssupporting
confidence: 92%
“…Our results are consistent with a study conducted in Brazil, which reported a prevalence of 4.4% [30]. Similarly, Iranian studies have reported prevalence rates of 3.1% and 1.8%, respectively [25][26][27][28][29][30][31][32] . whereas it is far a little bit with a study in Colombia, South America 0.29% 34 whereas with the results of CostRica study 19.23%.…”
Section: Resultssupporting
confidence: 92%